Perancangan Awal LKPD Berbasis Problem Solving pada Materi Bentuk Aljabar di SMP - Elie, Melkysedek; Djong, Kristoforus Djawa; Olla, Rinda (FARABI: Jurnal Matematika dan Pendidikan Matematika, 2025)
Mathematics instruction in Indonesia continues to encounter difficulties in cultivating students’ problem-solving abilities, particularly in topics related to algebraic expressions. This study seeks to examine instructional needs and to develop a problem-solving-oriented Student Worksheet (LKPD) tailored to algebraic form content. The research took place at SMP Negeri 6 Kupang Tengah Satu Atap, employing a Research and Development (R&D) methodology with a focus on the analysis and design phases of the ADDIE model. The participants were seventh-grade students. Data collection methods included classroom observations, teacher interviews, and document analysis. The analysis reveals that instruction remains predominantly teacher-centered, relying heavily on lectures, with low student engagement and a lack of supportive instructional media for fostering problem-solving. In response, a student worksheet was designed that incorporates Polya’s problem-solving framework and draws upon Kupang’s local context to enhance students’ problem-solving skills. This article reports on the needs assessment and the initial development of the worksheetTop of FormBottom of Form LKPD as the first step in developing contextual and meaningful teaching materials